Modern Teenager: Protest Demonstration and Attitude Towards Extremism - Fedotova A.V (Moscow State University of Psychology and Education, 2021)
The paper explores teenagers' attitude towards protest demonstration and exremism. The analysis is based on the data of a questionnaire survey carried out by the staff of the Centre of Sociology of Education (Institute of Education Management of the Russian Academy of Education).The survey involved 4873 students of grades 7th-11th of schools located in 3 regions of Russian Federation: Zabaikalsky Krai, Tulskaya oblast' and Smolenskaya oblast'. The data obtained in the research reveal specific gender and age differences. Male students choose active forms of protest whereas female students prefer discussions with friends and family or hiding their protest. The legitimate protest activity increases with age. The data showed that protest demonstration depend on student's social status: those with high status among classmates tend to choose active protest forms like participating in public protest events, appealing to the authorities, going to court. According to the survey teenagers' readiness to participate in active protest forms and involvement into extremist organizations' activity are connected to their activity in social media and aggressive behavior on the Internet (p≤0,05 for all comparisons). The results allow us to conclude that teenagers' protest activity and their involvement into extremist organizations' activity and attitude towards extremism are a part of their overall life position and determined by personal characteristics.